PERUBAHAN BENTUK PERTUNJUKAN TARI SEMBAH DALAM KONTEKS PARIWISATA DI KABUPATEN MUARA ENIM SUMATERA SELATAN - Treny Hera (Institut Seni Indonesia Surakarta, 2014)
Dance Sembah is a dance for welcoming the bridegroom’s parents in the wedding ceremony that early appearedin the village of Lubuk Empelas, Muara Enim, South Sumatra in 1956 by M. Natar. In 1989, the dancefunction changed to be a welcoming dance of a great guest. The dance, then, is creatively treated by Rasyid,one of dance artists from Muara Enim. He makes the choreography more interesting because the dance is inthe context of welcoming a guest. The change is focused on the movement, make up, and floor design.Dance Sembah has been continuously developing for the local government places it as their tradition inwelcoming important guests and in tourism sector, as the identity of Muara Enim residence.Keywords: dance Sembah, change of form